Informatics in Schools. Fundamentals of Computer Science and Software Engineering: 11th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2018, St. Petersburg, Russia, October 10-12, 2018, Proceedings - Pozdniakov, Sergei N; Dagienė, Valentina (LNCS sublibrary. SL 1, Theoretical computer science and general issues, 2018)
This book constitutes the proceedings of the 11th International Conference on Informatics in Schools: Situation, Evolution and Perspectives, ISSEP 2018, held in St. Petersburg, Russia, in October 2018.The 29 full papers presented in this volume were carefully reviewed and selected from 74 submissions. They were organized in topical sections named: role of programming and algorithmics in informatics for pupils of all ages; national concepts of teaching informatics; teacher education in informatics; contests and competitions in informatics; socio-psychological aspects of teaching informatics; and computer tools in teaching and studying informatics.